PENGARUH PERILAKU KEUANGAN, LITERASI KEUANGAN, DAN PENDAPATAN TERHADAP PERENCANAAN KEUANGAN PRIBADI - Sari, Atika; Yanti, Harti Budi (STMIK Widuri Jakarta, 2023)
Starting from the pandemic to rising prices for basic commodities, this creates financial problems and requires individuals to make financial planning. Researchers made this study with the aim of examining the effect of Financial Behavior, Financial Literacy, and Income on Personal Financial Planning. The researcher uses primary data collection techniques, in which the respondents to this study are undergraduate students who are already earning in Jakarta. The results of this study are that Financial Literacy has a positive effect on Personal Financial Planning. Meanwhile, financial behavior and income have no effect on personal financial planning. The researcher recommends for further research to further develop the research by adding samples and variables to further refine the research.